Visitors’ on-site wildlife viewing experience and becoming Africa in Asia: empirical evidence from Yala National Park, Sri Lanka - Ushantha, R.A.C.; Abdullah, N. H. B.; Lin, E. L. A.; Isa, S. S. B. (RSIS International, 2024)
Sri Lanka has recognized wildlife tourism as an industry that may be utilized to deviate from conventional tourism offerings. The country possesses all the necessary attributes to emerge as Asia’s next prominent wildlife destination, owing to its abundant natural resources. The key to achieving success in this endeavor is to offer a distinctive and quality wildlife experience for foreign visitors in the country’s national parks. The flagship of this expedition, according to numerous wildlife and tourism specialists, is Yala National Park.. Nevertheless, it is apparent that Yala National Park, the most frequented and highly regarded national park in Sri Lanka, is grappling with several significant challenges that adversely impact its global standing. It’s still unknown if these problems affect how visitors view the wildlife in national parks. Thus, this study explores the main obstacles Yala National Park in Sri Lanka has faced from stakeholders’ perspectives, how they affect park visitors’ on-site wildlife viewing experiences, and the nation’s efforts to become the world’s top wildlife tourism destination. This study is conducted as a qualitative study and employs a single-case design. Data was gathered through in-depth interviews with 18 participants from nine stakeholder categories. These participants were in Tissamaharama, the nearest town to Yala National Park. Participants identified eight distinct categories of significant issues faced by Yala National Park. The study findings disclosed that these crucial concerns have had a detrimental impact on the overall quality of on-site wildlife viewing for foreign tourists, undermining the country’s aspirations to be recognized as a premier global wildlife destination. The government and stakeholders of Yala National Park must comprehend this predicament swiftly. Resolving these vital concerns promptly is of utmost importance to enhance the on-site wildlife viewing experience for foreign visitors in Yala and position Sri Lanka as the Africa of Asia.